If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + -7) = 9x Reorder the terms: 6(-7 + x) = 9x (-7 * 6 + x * 6) = 9x (-42 + 6x) = 9x Solving -42 + 6x = 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -42 + 6x + -9x = 9x + -9x Combine like terms: 6x + -9x = -3x -42 + -3x = 9x + -9x Combine like terms: 9x + -9x = 0 -42 + -3x = 0 Add '42' to each side of the equation. -42 + 42 + -3x = 0 + 42 Combine like terms: -42 + 42 = 0 0 + -3x = 0 + 42 -3x = 0 + 42 Combine like terms: 0 + 42 = 42 -3x = 42 Divide each side by '-3'. x = -14 Simplifying x = -14
| 4=-(5v-6)+7v | | 2w+1w=45 | | -3x+7= | | 2(4x+3)=7x+13 | | 7a+12ab-(2a-b)+3b=0 | | 4=-(5-6)+7v | | 7x-2+2(x+4)+27=180 | | 840+.1x=(6000+x)(.12) | | 14x-14=11x+13 | | 0.5c-c= | | 6x+3-2=-5x+14 | | 2x-15=-17 | | 3x^2+11x+9=0 | | d^2=8d-16 | | L^2-15L+54= | | 3x-5=-5x+5 | | 3x+3x+10+4x=30 | | 4x+4y= | | 9x-4(x-6)=5x+4 | | -47-21n=58 | | -3(14+5r)-2r=-14(r+3) | | 2(5y+1)+2y= | | 12b+4=28 | | L(15-L)=54 | | 18=3(10-x)-5x | | 1.4+6.266n-7.9n=-3.6654 | | 9z^2-36z=0 | | x^2+12x=45 | | 0.24(18)+0.04x=0.08(18+x) | | 100[0.06(x+6)]= | | 5x^2+39x=8 | | 3x+x=188 |